1986
DOI: 10.1177/00220345860650111101
|View full text |Cite
|
Sign up to set email alerts
|

Arylaminopeptidase Activities of Oral Bacteria

Abstract: Protease and peptidase enzymes are thought to play a role in the virulence of many oral organisms, especially those associated with periodontal diseases. In order to evaluate the peptidases of periodontopathogens, we compared the arylaminopeptidase activities of Bacteroides gingivalis with those of other oral and non-oral bacteria. Sixty-three bacterial strains representing the prominent cultivable organisms in human periodontal pockets were tested, including representatives of the black-pigmented Bacteroides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 49 publications
9
51
1
Order By: Relevance
“…B. gingivalis was the only organism to cleave N-CBz-Gly-Gly-Argp-NA among black-pigmented Bacteroides strains tested (Nakamura et ah, 1984;Suido et aL, 1986). The present study showed similar results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…B. gingivalis was the only organism to cleave N-CBz-Gly-Gly-Argp-NA among black-pigmented Bacteroides strains tested (Nakamura et ah, 1984;Suido et aL, 1986). The present study showed similar results.…”
Section: Discussionsupporting
confidence: 82%
“…Peptidase activities were measured following the methods previously reported by Suido et al (1986) with some modifications. Reaction mixtures were prepared with 20 jxL of 1 mmol/L substrate, 80 |xL of 0.1 mol/L Tris-HCl buffer (pH 7.5), and 20 |xL of distilled water per well of a microtiter plate.…”
Section: Enzyme Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Gly-Pro-MCA by DPP4; LysAla-MCA by both DPP7 and DPP4; Met-Leu-, Gly-Phe-, LeuArg-, and Ser-Tyr-MCA by DPP7; and Leu-Asp-, Leu-Glu-, and Val-Asp-MCA by DPP11, whereas Leu-Gln-MCA may be cleaved by DPP7 because of its hydrophobic P2 preference (33). Several substrates such as Thr-Ser-and Gly-Gly-MCA were scarcely released by the bacterium, as suspected based on the substrate preferences of the 3 DPPs and a previous report that noted that no peptidase was found to be responsible for Thr, Ser, and Gly in P. gingivalis (34). Thr-Asp-and His-Asp-MCA were also scarcely hydrolyzed, because DPP11 prefers a hydrophobic P2 residue (24).…”
Section: Dipeptide Production In P Gingivalis Wild Type and Kdp136-mentioning
confidence: 81%
“…dentin specimens similar to those used in this study were incubated with trypsin at 37°C which resulted in a collagen loss of 70% within 24 h. Nonspecific proteolytic enzymes are pro duced by several bacterial species. Ova et al [1971], Andersson et al [1984] and Suido et al [1986] found aminopeptidase activity, which may be involved in the degrada tion of the organic matrix, in lactobacilli and strains of S. mitis and Streptococcus sanguis. Larmas et al [1986] found histochemical evidence for the occurrence of aminopeptidases in human carious dentin, which were of mi crobial origin [Larmas and Mäkinen.…”
Section: Discussionmentioning
confidence: 99%